2020
DOI: 10.18844/cjes.v15i1.4461
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between self-regulated learning strategies, learning motivation and mathematics achievement

Abstract: This study aimed at examining the relationships of self-regulated learning strategies with students’ learning motivation and academic achievement in mathematics. The study employed a descriptive research design. The participants were 238 ninth grade students in the Sultanate of Oman. The Motivated Strategies for Learning Questionnaire was used to assess the participants’ use of self-regulated learning strategies and motivation. Academic achievement was reflected by the total score obtained in mathematics. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 24 publications
11
47
1
10
Order By: Relevance
“…Analysis of the results of the diagnostic phase of our study allows us to draw the following conclusions; -first-graders of both groups with intellectual disabilities expressed systemic underdevelopment of speech, lack of communication skills; -the revealed features of communicative disorders in mentally retarded first-graders aim at the illegality of the information of the entire content of speech therapy work with this category of children only to the correction of phoneticphonemic and lexical-grammatical means of the language; the failure of mentally retarded younger students in the field of speech communication is associated not only with the systemic underdevelopment of speech, but also, most importantly, with the lack of communication skills, in particular, with the inability to understand the situation of communication, take into account the characteristics of the partner, arbitrarily use the available verbal and non-verbal means for communication; it is necessary to work purposefully and consistently on the formation of means of communication, communication skills El-Adl, & Alkharusi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the results of the diagnostic phase of our study allows us to draw the following conclusions; -first-graders of both groups with intellectual disabilities expressed systemic underdevelopment of speech, lack of communication skills; -the revealed features of communicative disorders in mentally retarded first-graders aim at the illegality of the information of the entire content of speech therapy work with this category of children only to the correction of phoneticphonemic and lexical-grammatical means of the language; the failure of mentally retarded younger students in the field of speech communication is associated not only with the systemic underdevelopment of speech, but also, most importantly, with the lack of communication skills, in particular, with the inability to understand the situation of communication, take into account the characteristics of the partner, arbitrarily use the available verbal and non-verbal means for communication; it is necessary to work purposefully and consistently on the formation of means of communication, communication skills El-Adl, & Alkharusi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Problem-solving abilities in adolescents who have a relationship with intrinsically high motivation with a healthy and appropriate humour style (Nayir, 2017;Ridha et al, 2019). Intrinsic motivation, extrinsic motivation has a positive relationship with self-regulated learning (El-Adl & Alkharusi, 2020) The second discovery stated that a relationship exists between metacognitive awareness and problem-solving ability of civic education, and it is observed in the sig. value of 0.000, which is smaller than 0.05.…”
Section: Simultaneous Relationship Between Predictor Variables and Prmentioning
confidence: 99%
“…Past studies showed that students’ learning motivation impacts teaching results ( Law et al, 2019 ; Sanaie et al, 2019 ). El-Adl and Alkharusi (2020) also believed that learning motivation is the motivation of achievement for learners to maintain their learning activities in their learning processes. It is one of the critical factors affecting learning performance ( Rocha et al, 2019 ; Gan, 2020 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%